Productive Yield, Composition and Nutritional Value of Housefly Larva Meal Reared in High-Altitude Andean Zones of Peru - Ochoa, Isai (2026)
This study evaluated the productivity, nutritional composition, amino acid profile, fatty acid profile and presence of Salmonella spp. of housefly larva meal reared on domestic animal manure. A study was conducted to produce larva on three types of manure in a controlled environment located at 3200 mASL. Adult flies used as brood stock were reared in advance to avoid contamination with pathogenic germs and were fed sugar syrup and pasteurized milk to promote oviposition. Data were analyzed by ANOVA, the Kruskal–Wallis test and descriptive statistics, using confidence intervals. The results indicate that the type of organic substrate had an effect on the time of development, weight, size and percentage mortality of larva, being higher in a mixture of swine manure and poultry manure. Regarding nutritional composition, it was determined that larva meals contain 56.5% crude protein, 13.07% fat, 12.03% carbohydrates, 10.93% ash and 6.77% crude fiber. The most abundant fatty acids are palmitic acid with 29.34%, palmitoleic acid with 21.65% and oleic acid with 26.53%. An adequate balance of amino acids was determined, highlighting among them the content of arginine and threonine within the essential amino acids. House fly larva meals contain an adequate balance of nutrients and can be used as an ingredient for animal feed formulation. However, their use in animals should be further evaluated in future studies to assess their viability, absorption, bioavailability, and potential allergic reactions.